Session 9 [videorecording (DVD)] - Anderson, Brad, 1964-; Caruso, David, 1956-; Mullan, Peter; Sexton, Brendan, 1980-; Gevedon, Stephen, 1966-; Lucas, Josh (Universal/USA Films, 2002)
The Danvers State Mental Hospital, closed for fifteen years, is about to receive five new visitors. The men of the Hazmat Elimination Co. venture into the vacant asylum filled with an evil past of patient abuse, medieval medical procedures and rumors of demonic possession. But each of the men hold secrets as well.